2011
DOI: 10.1089/jpm.2010.0299
|View full text |Cite
|
Sign up to set email alerts
|

Assessing End-of-Life Preferences for Advanced Dementia in Rural Patients Using an Educational Video: A Randomized Controlled Trial

Abstract: Rural subjects with higher health literacy were more likely to want comfort care compared to those with lower levels of health literacy. Furthermore, subjects who viewed a video decision aid were more likely to opt for comfort compared to those who solely listened to a verbal description. These findings suggest that video can help elicit preferences and that interventions to empower such patients need to be designed in a manner that is sensitive to health literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(124 citation statements)
references
References 33 publications
2
121
0
1
Order By: Relevance
“…Second, level of education was used in one study as an indicator of HL despite the fact that: (1) the relationship between HL and level education has been disputed in the literature, and (2) three studies included in this review reported a lack of correlation, or congruence, between level of education and level of HL 15 [18,34,51]. Third, in four studies, the care or treatment preferences of patients were elicited using PDAs that reflected a medical condition that most, if not all, patients in the study population did not have at the time of the study [38,39,40,41]. The majority of patients in these studies, therefore, were making hypothetical treatment, or care, decisions.…”
Section: Findings Relevant To the Deciding On The Treatment To Implemmentioning
confidence: 98%
See 2 more Smart Citations
“…Second, level of education was used in one study as an indicator of HL despite the fact that: (1) the relationship between HL and level education has been disputed in the literature, and (2) three studies included in this review reported a lack of correlation, or congruence, between level of education and level of HL 15 [18,34,51]. Third, in four studies, the care or treatment preferences of patients were elicited using PDAs that reflected a medical condition that most, if not all, patients in the study population did not have at the time of the study [38,39,40,41]. The majority of patients in these studies, therefore, were making hypothetical treatment, or care, decisions.…”
Section: Findings Relevant To the Deciding On The Treatment To Implemmentioning
confidence: 98%
“…Third, some measures of HL were used in an inconsistent manner across studies, making comparisons of the findings difficult. For example, the original four categories of the REALM (i.e., 0-3 rd grade, 4 th -6 th grade, 7 th -8 th grade, 9 th grade and above) were used in some studies [22,33,34,35,36,37], but were reduced to three [38,39,40,41] or two [14,15,42,43,44,45,46,47] in others -with some loss of information and thus implications for the validity of the findings. In two studies, the REALM was treated as a continuous variable [16,48].…”
Section: Definitions and Measures Of Hlmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Current estimates indicate that only 41% of the population in Australia have the required level of literacy to share in decisions about complex health treatment. 16 Despite this, there is evidence that clinicians over estimate patient levels of health literacy. 52 The reasons for low health literacy are multi-factorial, but many relate to patient characteristics such as low socioeconomic status, differing cultural backgrounds or health conditions such as dementia.…”
Section: Health Literacymentioning
confidence: 99%
“…15 Current estimates indicate that only 41% of the Australian population have the required level of health literacy to share in complex decisions about health treatment. 16 Intervention, such as patient decision aids have shown promise in ameliorating health literacy barriers. 17 Initially shared decision making focused on the medical practitioner/patient dyad, 18 but more recent commentary proposes that it is relevant to all clinicians, in all disciplines.…”
Section: Introductionmentioning
confidence: 99%